Community Forum Identifies Opportunities to Engage with Eastern Kentucky Community Leaders about Chronic Disease and Environmental Pollution - Brewer, Dawn (Appl Environ Educ Commun, 2019)
The NIEHS-sponsored Appalachian Health & Well-Being Community Forum held in Eastern Kentucky brought various community members together to communicate and establish better coordination of efforts to improve health and address regional environmental issues. The two-hour forum discussion provided bi-directional feedback about the needs and interests of community members. Top concerns of community members included obesity and obesity-related diseases and environmental pollution. Healthful lifestyles were identified as part of the remedy to protect health from potential adverse health effects associated with environmental pollution. This study highlights opportunities to engage with Appalachian communities around topics related to health and environmental pollution.